Enhancement of efficiency of technological depart ments management in an individual and small-scale production company - B.V. Palyukh; G.B. Burdo (Advanced Engineering Research)
The paper shows the results of research on relations between elements of production system of machine-building plants with individual and small-scale production from the position of process management. It specifies the main principles used when creating integrated systems of process planning and management.